2022
DOI: 10.3390/children9060774
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Characteristics and Experiences in Patients with Multiple Endocrine Neoplasia Type 2 (MEN2) and Medullary Thyroid Carcinoma (MTC)

Abstract: Multiple Endocrine Neoplasia type 2 (MEN2) is a genetic cancer syndrome for which there are limited data pertaining to the quality of life and psychosocial experiences of persons affected. Medullary thyroid carcinoma (MTC) is a rare disease of the thyroid gland often associated with MEN2. MTC often progresses slowly and may present with a myriad of physical symptoms including hair loss, sleep disturbance, fatigue, weight changes, heart palpitations, and constipation or diarrhea. Like other cancers or rare, inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Similarly, through data collected via a structured psychosocial interview and the Distress Thermometer/Problem Checklist, Lockridge and colleagues [ 3 ] found that patients ( n = 63) with Multiple Endocrine Neoplasia 2 (MEN2B) and Medullary Thyroid Carcinoma (MTC) identified the need for information about available services and education about MTC as high-priority. MEN2 is a genetic cancer syndrome for which there are limited data pertaining to the quality of life and psychosocial experiences of persons affected.…”
Section: Contributions To the Special Issuementioning
confidence: 99%
“…Similarly, through data collected via a structured psychosocial interview and the Distress Thermometer/Problem Checklist, Lockridge and colleagues [ 3 ] found that patients ( n = 63) with Multiple Endocrine Neoplasia 2 (MEN2B) and Medullary Thyroid Carcinoma (MTC) identified the need for information about available services and education about MTC as high-priority. MEN2 is a genetic cancer syndrome for which there are limited data pertaining to the quality of life and psychosocial experiences of persons affected.…”
Section: Contributions To the Special Issuementioning
confidence: 99%